A woman's place is in theatre: women's perceptions and experiences of working in surgery from the Association of Surgeons of Great Britain and Ireland women in surgery working group. Issue 1 (7th January 2019) - Bellini, Maria Irene; Graham, Yitka; Hayes, Catherine; Zakeri, Roxanna; Parks, Rowan; Papalois, Vassilios
Abstract : Objective: Surgery remains an inherently male-dominated profession. The aim of this study was to survey women working within the discipline, to understand their current perceptions, providing insight into their practical day-to-day lives, supporting an action-oriented change. Design and setting: The link to a confidential, online survey was distributed through the Association of Surgeons of Great Britain and Ireland (ASGBI) social media platforms on Facebook and Twitter over a 2-week period in October 2017. Participants: Women working in surgical specialties and actively responding to the link shared through the ASGBI social media platforms. No patients were involved in the study. Primary and secondary outcome measures: Data were analysed through a mixed-methods approach. The quantitative data were analysed through descriptive statistics and qualitative analysis was undertaken using a constant comparative analysis of the participants' comments, to identify salient patterns (themes). Results: A total of 81 female participants replied (42% response rate based on the Facebook group members), with 88% (n=71) perceiving surgery as a male-dominated field. Over half had experienced discrimination (59%, n=47), while 22% (n=18) perceived a 'glass ceiling' in surgical training. Orthopaedics was reported as the most sexist surgical specialty by 53% (n=43). Accounts of gendered language in the workplace were reported by 59% (n=47), with 32% (n=25) of surveys participants having used it. Overall, a lack of formal mentorship, inflexibility towards part-time careers, gender stereotypes and poor work–life balance were the main perceived barriers for women in surgical careers. Conclusion: These findings highlight the implicit nature of the perceived discrimination that women report in their surgical careers. The ASGBI acknowledges these perceptual issues and relative implications as the first of many steps to create an action-oriented change by allowing all staff, regardless of gender, to reflect on their own behaviour, perceptions and the culture in which they work.